Financial reporting - Alexander, David (Thomson Learning, 2001)
This edition of the text combines financial accounting theory with a detailed examination of the legal and regulatory framework of accounting. Its scope is wide enough to be of use to MBA and professional students as well as 2nd and 3rd years